(untitled) (Journal of Pharma Insights and Research, 2025)
A Quality by Design (QbD) approach was used to develop and validate three UV spectrophotometric methods for the simultaneous quantification of Paracetamol (PCM) and Ibuprofen (IBU) in pharmaceutical formulations. The developed methods consisted of gradient UV method, simultaneous equation method, and absorbance ratio method (Q-analysis). The critical method parameters were optimized using Design Expert® software with central composite design. The developed methods exhibited linearity in the range of 2-20 μg/mL for IBU and 2-14 μg/mL for PCM. The methods showed good precision with %RSD values less than 2%. Recovery studies yielded results between 96.36-100.58%, indicating good accuracy. The LOD values were found to be 0.546-1.287 μg/mL for IBU and PCM respectively, while LOQ values ranged from 0.142-0.602 μg/mL. Critical parameters identified through principal component analysis included sample preparation, slit width (1.0), scan speed (medium), and sampling interval (1.0). The methods were validated according to ICH Q2(R1) guidelines for specificity, linearity, precision, accuracy, robustness and ruggedness. All three methods proved suitable for routine quality control analysis of PCM and IBU in combined pharmaceutical formulations, offering advantages of simplicity, accuracy and reproducibility